Intimidades violentas - Timm, Flávia Bascuñán (2017)
This work constitutes a study of the relations of power that forged the myth of romantic love and that produced effects of subjectivation in the minds and bodies of lovers. These effects are still present in ideas that circulate in contemporaneity. The theoretical path chosen to discuss violent relations established in romantic love have been the presentation of relation between the notion of the modern individual and hyperinvestment in intimacy as a molar force in the history of modern thought. The study was based on Foucault's genealogical method and on the historical and critical analyses of Richard Sennett and Alain Renaut, as well as on contributions to an active way of life, based on Espinosa's ethics, Foucault's concept of self-care and Braidotti’s nomadism. This thesis develops the concepts of “love-norm” and “loveexperience”. The aim was to display, in the discourse of intimacy, the operation of desire and power in the production of romantic love ideal and its relation with the intimate partner violence.